ANALISIS KESALAHAN BERDASARKAN TAHAPAN NEWMAN DALAM MENYELESAIKAN SOAL APLIKASI TURUNAN BAGI PESERTA DIDIK KELAS XII SMA NEGERI 1 BUKITTINGGI - Fadhilatul Husna (Departemen Matematika, 2022)
The results of the Final Semester Assessment which are still low show that students still make many mistakes in solving math problems. For this reason, it is necessary to analyze the types of errors and the factors that cause students’ mistakes in solving math problems. This study aims to describe and analyze the errors of class XII students of SMA Negeri 1 Bukittinggi in application of trigonometric function derivatives based on Newman's error analysis. The type of research is descriptive with the subjects are students of class XII IPA 9, totaling 36 students. The data was collected by giving the application test of trigonometric function derivatives and interviews. Furthermore, nine students were selected to be interviewed. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The data validity technique is triangulation technique. The results showed that the most mistakes made by students were encoding error with an error percentage of 43.62%. Then, the transformation error 17.02%, the process skill error is 15.96%, reading comprehension error is 13.23%, and reading error by 10.64%. Internal factors that cause students’ mistakes include interest/motivation to learn, study habits, students' ability to solve problems, carelessness, etc. The external factor that causes students’ mistakes is the learning process in the classroom.Keywords - Error analysis, math problems, Newman’s analysis, application of derivatives